2007
DOI: 10.1016/j.jaut.2007.04.001
|View full text |Cite
|
Sign up to set email alerts
|

Large functional repertoire of regulatory T-cell suppressible autoimmune T cells in scurfy mice

Abstract: Scurfy mice which lacks functional Foxp3 transcription factor and CD4(+)CD25(+)Foxp3(+) regulatory T (Treg) cells, spontaneously develop autoimmune responses against skin, lung, liver and tail. However, many organs/tissues are spared from autoimmune attack. Here, we demonstrate that scurfy mice contain dormant autoimmune T cells that induced new diseases such as sialoadenitis, dacryoadenitis, pancreatitis, gastritis, intestinal inflammation, colitis, and myositis in RAG-1 KO mice. Inflammation in as many as 12… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
72
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 50 publications
(74 citation statements)
references
References 40 publications
2
72
0
Order By: Relevance
“…This strategy results in a mouse with an intact innate immune system, T cells and B cells, but devoid of FoxP3 ϩ Tregs. 25 These Treg-deficient mice were found to be significantly more sensitive to kidney IRI, adding further support to the hypothesis that Tregs are protective in this setting. To confirm the importance of Tregs, we co-administered highly pure isolated Tregs with Sf LN cells, which were sufficient to inhibit IRI significantly compared with Treg-deficient mice.…”
Section: Cd25mentioning
confidence: 65%
See 1 more Smart Citation
“…This strategy results in a mouse with an intact innate immune system, T cells and B cells, but devoid of FoxP3 ϩ Tregs. 25 These Treg-deficient mice were found to be significantly more sensitive to kidney IRI, adding further support to the hypothesis that Tregs are protective in this setting. To confirm the importance of Tregs, we co-administered highly pure isolated Tregs with Sf LN cells, which were sufficient to inhibit IRI significantly compared with Treg-deficient mice.…”
Section: Cd25mentioning
confidence: 65%
“…In addition, in the adoptive transfer experiments, the Tregs, which were selected on the basis of CD25 expression, were competent to reduce kidney IRI in these models and prevent Sf LN cell-mediated multiorgan damage in a previous study. 25 These findings suggest that Treg CD25 expression is an important phenotypic marker for protection against kidney IRI.…”
Section: Cd4mentioning
confidence: 92%
“…However, if IL-2 was required for thymic-negative selection of autoimmune T cells against self Ags (37), one would expect that Sf.Il2 Ϫ/Ϫ mice should have more autoimmune T cells against ear, skin, and lung, an interpretation incompatible with our results. Moreover, because the autoimmune T cell repertoire in Treg-deficient strains is potentially very large (32), it is also difficult to envisage a mechanism of IL-2-dependent thymic selection that controls organ-specific autoimmune T cells as a whole. It remains possible that the high-affinity IL-2/IL-2R signaling is required for the expansion of certain low-affinity autoimmune T cells whose threshold of activation is high (39).…”
Section: Discussionmentioning
confidence: 99%
“…These observations indicate that IL-2 is required for the severe autoimmune responses manifested in the lung and skin of Sf mice. Our previous study has shown that Sf mice contain dormant autoimmune T cells that can be revealed by adoptive transfer experiments (32). Therefore, lymph nodes cells from Sf.Il2 Ϫ/Ϫ mice were adoptively transferred into RAG1 Ϫ/Ϫ recipients and organ inflammation was determined 4 wk later (Fig.…”
Section: Il2 ϫ/ϫ But Not Fas Lpr/lpr Mutation Regulates Organ-specifimentioning
confidence: 98%
“…2), consistent with a previous finding that i.m. injection of lymphocytes of Foxp3-deficient scurfy mice, in which IL-21-producing CD4 + T cells are significantly increased (21), into RAG-deficient mice causes IM-like pathological changes (44,45). Taken together, these findings suggest that IL-21 plays a pathogenic role in IM in mice, and possibly in humans, and could be a therapeutic target for IM.…”
Section: Discussionmentioning
confidence: 76%